CATATAN KRITIS TERHADAP POLITISASI BIROKRASI DALAM PEMILU - Enny Suryanjari (Badan Kepegawaian Negara | The National Civil Service Agency, 2009)
Undang-Undang No.43 Tahun 1999 Tentang Pokok-pokok Kepegawaian Negara rules how to make bureaucratic independenly. But in fact, the process of democratic showed many problematic situations of bureaucratic reform in Indonesia. This paper show that the political reform and democratization do not guarantee the neutrality of bureaucracy. Many evidence show that in reform era we still found the political cooptation in the bureaucratic system.Key words: bureaucracy, civil servants, election